2021
DOI: 10.1155/2021/5582547
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Practice and Associated Factors among Hypertensive Patients in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Background. Hypertension is one of the leading causes of morbidity and mortality in developing countries including Ethiopia. Self-care practice has been provided as one of the most important preventive mechanisms of hypertension and is considered as a basic treatment for hypertension. There is no national-level study that assesses hypertensive self-care practice in Ethiopia. Therefore, this study aimed to assess the pooled level of hypertensive self-care practices and associated factors in Ethiopia. Methods. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…An unhealthy lifestyle is a significant factor causing uncontrolled blood pressure. Therefore, it is necessary to consistently provide health education about healthy lifestyle practices in patients with hypertension [26] This study also found a relationship between knowledge and adherence to physical activity. Studies report insufficient knowledge of the appropriate duration of physical exercise.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…An unhealthy lifestyle is a significant factor causing uncontrolled blood pressure. Therefore, it is necessary to consistently provide health education about healthy lifestyle practices in patients with hypertension [26] This study also found a relationship between knowledge and adherence to physical activity. Studies report insufficient knowledge of the appropriate duration of physical exercise.…”
Section: Discussionmentioning
confidence: 51%
“…Knowledge is the basis for a person to practice self-care so that knowledge is positively correlated with self-care for people with hypertension [19], [26], [27]. Better knowledge leads to better practice in some ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10 Furthermore, self-care is impacted by variables including formal education, knowledge about hypertension, and social support. 11 Recognized as the primary treatment and preventive measure for hypertension, self-care is considered the significant importance in its management. 12 Taken together, self-care behavior may mediate the association between health literacy and BP control.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with a previous study, suggesting that overall hypertension self-management was generally adequate. This outcome may be attributed to the cumulative effect of years of exposure to both passive and active health education and counseling initiatives worldwide, wherein patients have reported a high level of satisfaction with the care provided for their blood pressure control (Konlan & Shin, 2023 ; Oluwole et al, 2019 ; Wondmieneh et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%